Case Report: Identification of Eimeria tenella Infection and Pathologic Changes in a Broiler Chicken in Kutuh Village Farm, Badung, Bali - Putra, I Putu Cahyadi; Sari, Ni Komang Wahyu Centika; Kardena, I Made; Besung, I Nengah Kerta (Universitas Pendidikan Mandalika, 2025)
Coccidiosis is a serious parasitic disease of chickens caused by the protozoan Eimeria, with Eimeria tenella being one of the most virulent species. The infection causes necrosis and hemorrhage of the large intestine, resulting in significant economic losses in the poultry industry. The purpose of this case report was to determine the cause of death of broiler chickens in one farm in Kutuh Village, South Kuta Subdistrict, Badung Regency. The case animal (protocol number 39/N/24) was a 20-day-old broiler from the farm with a population of 18,000 birds. The examination process included anamnesis, clinical signs, anatomical pathology, histopathology, bacteriology, parasitology (including coprology and McMaster techniques), and morphometric identification of Eimeria tenella using ImageJ software. The clinical signs observed included anorexia, weakness, dull feathers, and reddish feces with a porridge-like consistency. Pathological examination revealed alterations in the cecum and colon. Histopathological analysis indicated typhlitis hemorrhagis et necrotican and colitis necrotican. Bacteriological examination revealed Escherichia coli, a normal flora, in the caecum and colon. Morphological and morphometric analyses of the oocysts revealed that E. tenella is ovoid, with two wall layers, an average size of 21.670 × 19.942 μm, and an oocyst count of 188,600 per gram of feces (OPG). The cause of death of the case chickens was due to severe Eimeria tenella infection.